Effects of plasma treatment on surface properties of ultrathin layered MoS2. (1st July 2016) - Kim, Suhhyun; Choi, Min Sup; Qu, Deshun; Ra, Chang Ho; Liu, Xiaochi; Kim, Minwoo; Song, Young Jae; Yoo, Won Jong
Abstract: This work investigates the use of oxygen plasma (O2 ) treatment, applied as an inductively coupled plasma, to control the thickness and work function of a MoS2 layer. Plasma-etched MoS2 exhibited a surface roughness similar to that of the pristine MoS2 . The MoS2 field effect transistors fabricated using the plasma-etched MoS2 displayed a higher n-type doping concentration than that of pristine MoS2 . The x-ray photoelectron spectroscopy was performed to analyze chemical composition to demonstrate the minimum level of chemical reactions occurred upon plasma treatment. Moreover, Kelvin probe force microscopy measurements were conducted to probe the changes in the work function that could be attributed to the changes in the surface potential. The measured work functions suggest the modification of a band structure and n-doping effect after plasma treatments that depended on the number of MoS2 layers. This study suggests that the O2 plasma can control the layer number of the MoS2 as well as the electronic properties of a MoS2 film.